OPINIONS OF HIGH SCHOOL TEACHERS RELATED WITH THE IMPLEMENTATION LEVEL OF FATIH PROJECT AND REFLECTION COMPETENCE IN THEIR COURSES: A CASE OF KIRŞEHİR PROVINCE - Mustafa YAĞCI (International Journal of Eurasia Social Sciences, 2016)
The rapid developing technology affects every field of our life. The development of the technology forms a basis for carrying the education to the forward. The most important step in this matter is “Movement of Increasing Opportunity and Developing Technology (FATİH)” Project. Within the scope of this project, the interactive association of the teachers and students aims the students to develop themselves in more qualified education environment. For actualization of the aim, the teacher must have the sufficient knowledge for the usage of the tools used within the scope of FATIH project. The purpose of this study is to determine the opinions of the teacher related with the implementation level of FATIH project and reflection competence in their courses. The research is limited with 240 high school teachers working in 10 different high school in central district of Kırşehir province. According to the results of the research, the opinions of the teachers related with the implementation level of FATIH Project, are in medium level. Besides, the opinions of teachers related with the implementation level of FATIH Project, show statistically significant difference according to the e-content usage of the scale and gender in institution competence size, marital status in whole sub-dimensions and e-content usage, in self-competence, project return and institution competence size, according to the age and occupational seniority variables.